Proceedings of the 2003 International Symposium on Circuits and Systems, 2003. ISCAS '03.
DOI: 10.1109/iscas.2003.1205152
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired optical flow circuits for the visual guidance of micro air vehicles

Abstract: In 1986, Franceschini et al. built an optronic velocity sensor [11], the principle of which was based on the findings they had recently made on fly EMDs by performing electrophysiological recordings on single neurons while concomitantly applying optical microstimuli to single photoreceptor cells [12]. As early as 1989, a battery of 110 velocity sensors of this kind was used to enable a small autonomous mobile robot to steer its way through an unknown field full of obstacles at a relatively high speed (50 cm/s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 17 publications
1
61
0
1
Order By: Relevance
“…For example, some authors [55][56][57] have resorted to using the multiple optic flow sensors found in computer optical mice. Whereas others 68,69 have developed neuromorphic chips that not only extract optic flow, but also adapt to the large variety of light intensities that can be experienced when flying in confined spaces. Similarly, specialized micro optic flow sensors have been used for altitude regulation in sub-1 g flying robots 70 .…”
Section: Review Insightmentioning
confidence: 99%
“…For example, some authors [55][56][57] have resorted to using the multiple optic flow sensors found in computer optical mice. Whereas others 68,69 have developed neuromorphic chips that not only extract optic flow, but also adapt to the large variety of light intensities that can be experienced when flying in confined spaces. Similarly, specialized micro optic flow sensors have been used for altitude regulation in sub-1 g flying robots 70 .…”
Section: Review Insightmentioning
confidence: 99%
“…This fly-inspired 2-pixel local motion sensor assesses the optic flow on the basis of the inverse of the delay between the detection of the same contrasting feature by two adjacent photoreceptors [24,43]. This 1D optic flow estimation method is largely invariant to contrast and spatial frequency [1].…”
Section: Optic Flow-based Visual Guidance Above An Unsteady Platformmentioning
confidence: 99%
“…During the last decade, some fixedand rotary-wing aerial robots have been equipped with similar means of detecting and processing the OF to those providing insects such as flies and bees with the vital cues they need to take off, follow a terrain and land (blimp: [19], fixed-wings: [8,[20][21][22], rotary-wings: [1,2,9,[23][24][25]), to hover (rotary-wings: [10,26,27]), and to track a moving target (rotary-wings: [27][28][29]). In aerial robots, OF processing methods were used in several ways as ameans of:…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a second order fixed-point low pass filter was used to enhance the signal to noise ratio by removing the noise remaining at frequencies of more than 10 Hz. The algorithm called the "Time of travel scheme" implemented here consists mainly of a hysteresis thresholding process with separate ON and OFF pathways [5,39,40,42,45] followed by the ∆t computation, the result of which is fed into a corresponding table. Lastly, the five simultaneously computed optic flows ω m i are combined by the median operator in order to increase the robustness and the refresh rate of the output [40].…”
Section: % (Rmentioning
confidence: 99%